Rhizosphere priming effects in soil aggregates with different size classes. Issue 2 (12th February 2020) - Wang, Xiaohong; Dijkstra, Feike A.; Yin, Liming; Sun, Di; Cheng, Weixin
Abstract: The change in native soil organic carbon (SOC) decomposition caused by plant roots or the rhizosphere priming effect (RPE) is a common phenomenon. Although most of the SOC is stored in aggregates with different size classes, the RPE in aggregates and the underlying mechanisms remain unclear. In a 35‐d pot experiment, we grew Agropyron cristatum (C3 plant) in pots containing large macroaggregates (LMA), small macroaggregates (SMA), and microaggregates (MA) separated from a C4 soil. We quantified the RPE and measured microbial biomass C (MBC), oxidase activity, soil net nitrogen (N) mineralization, and aggregate dynamics at the end of the experiment. The positive RPEs ranged from 47% to 106% and were significantly lower in the SMA treatment than in the LMA and MA treatments. Planting significantly increased microbial N immobilization in all treatments, particularly in the SMA treatment. Furthermore, the positive relationship between RPE and plant‐induced changes in net N mineralization suggests that increasing microbial N immobilization could reduce RPE. Planting significantly increased MBC and oxidase activity, and the positive relationships between SOC decomposition and MBC and oxidase activity suggest that microbial activation may play an important role in the positive RPEs. Planting significantly reduced aggregate destruction in the SMA treatment but increased aggregate destruction in the MA treatment, supporting the aggregate destruction hypothesis. Overall, our results showed for the first time that the RPEs varied among aggregate size classes, with potentially important consequences for SOC dynamics in soils that have a high capacity for aggregation.